ESPGHAN Position Paper on Management of Percutaneous Endoscopic Gastrostomy in Children and Adolescents. Issue 1 (January 2015) - Heuschkel, R.B.; Gottrand, F.; Devarajan, K.; Poole, H.; Callan, J.; Dias, J.A.; Karkelis, S.; Papadopoulou, A.; Husby, S.; Ruemmele, F.; Schäppi, M.G.; Wilschanski, M.; et al.
ABSTRACT Objectives: This European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) position statement provides a comprehensive guide for health care providers to manage percutaneous endoscopic gastrostomy tubes in a safe, effective, and appropriate way. Methods: Relevant literature from searches of PubMed, CINAHL, and recent guidelines was reviewed. In the absence of evidence, recommendations reflect the expert opinion of the authors. Final consensus was obtained by multiple e-mail exchange and during 3 face-to-face meetings of the gastroenterology committee of the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition. Results: Endoscopically placed gastrostomy devices are essential in the management of children with feeding and nutritional problems. The article focuses on practical issues such as indications and contraindications. Conclusions: The decision to place an endoscopic gastrostomy has to be made by an appropriate multidisciplinary team, which then provides active follow-up and care for the child and the device.